Putting trajectories to work: translating a HCI framework into design practice - Velt, Raphael (2018)
One major challenge for the academic Human-Computer Interaction (HCI) research community is the adoption of its findings and theoretical output by the interaction design practitioners whose work they are meant to support. To address this “research-practice gap”, this thesis takes the example of trajectories, a HCI conceptual framework derived from studies of mixed-reality performances spanning complex spaces, timeframes, participant roles, and interface ecologies. Trajectories’ authors have called for their work to be used to inform the design of a broader variety of experiences. This thesis explores what is required to fulfil this ambition, with a specific focus on using the framework to improve the experience of live events, and on professional design practitioners as the users of the framework. This exploration follows multiple approaches, led both by researchers and practitioners. This thesis starts by reviewing past uses of the trajectories framework – including for design purposes – and by discussing work that has previously tried to bridge the research-practice gap. In a first series of studies, the thesis identifies live events – such as music festivals and running races – as a rich setting where trajectories may be used both to study existing experiences and to design new ones. This leads to a series of design guidelines grounded both in knowledge about the setting and in trajectories. The thesis then discusses multiple approaches through which HCI researchers and practitioners at a large media company have joined forces to try to use trajectories in industrial design and production processes. Finally, the last strand of work returns to live events, with a two-year long Research through Design study in which trajectories have been used to improve the experience of a local music festival and to develop a mobile app to support it. This last study provides first-hand insight into the integration of theoretical concerns into design. This thesis provides three major classes of contributions. First, extensions to the original trajectories framework, which include refined definitions for the set of concepts that the framework comprises, as well as considerations for open-ended experiences where control is shared between stakeholders and participants. Secondly, a model describing the use of trajectories throughout design and production processes offers a blueprint for practitioners willing to use the framework. Finally, a discussion on the different ways trajectories have been translated into practice leads to proposing a model for locating translations of HCI knowledge with regards to the gap between academic research and design practice, and the gap between theoretical knowledge and design artefacts.